FILSAFAT DAKWAH YANG TERABAIKAN - Lutfi Ulfa Ni’amah (IAIN Tulungagung, 2016)
The development philosophy seems to ignore the dakwah. Similarly, dakwah does not need philosophy. Therefore, compared with other fields of philosophy, philosophy of preaching is not so interesting discussion. This article attempts to dig more development and philosophy of dakwah. This article also shows the urgency of philosophy preaching to the effectiveness of dakwah in society. Therefore, the call is not simply convey religious advice, but also involved in resolving social problems.Keywords: Dakwah, philosophy, development